Spin transport properties of single metallocene molecules attached to single-walled carbon nanotubes via nickel adatoms - SANVITO, STEFANO (My University, 2011)
The spin-dependent transportproperties of single ferrocene, cobaltocene, and nickelocene molecules attached to the sidewall of a (4,4) armchair single-walled carbon nanotube via a Ni adatom are investigated by using a self-consistent ab initio approach that combines the non-equilibrium Green's function formalism with the spin density functional theory. Our calculations show that the Ni adatom not only binds strongly to the sidewall of the nanotube, but also maintains the spin degeneracy and affects little the transmission around the Fermi level. When the Ni adatom further binds to a metallocene molecule, its density of states is modulated by that of the molecule and electron scattering takes place in the nanotube. In particular, we find that for both cobaltocene and nickelocene the transport across the nanotube becomes spin-polarized. This demonstrates that metallocene molecules and carbon nanotubes can become a promising materials platform for applications in molecular spintronics.
PUBLISHED
Keywords: Physics; Nanoscience & Materials